Whole-fat dairy products do not adversely affect adiposity or cardiometabolic risk factors in children in the Milky Way Study: a double-blind randomized controlled pilot study. Issue 6 (11th October 2021) - Nicholl, Analise; Deering, Kane E; Evelegh, Kate; Lyons-Wall, Philippa; Lawrence, David; Mori, Trevor A; Kratz, Mario; O'Sullivan, Therese A
ABSTRACT: Background: Limited evidence supports the common public health guideline that children >2 y of age should consume dairy with reduced fat content. Objectives: We aimed to investigate the effects of whole-fat compared with reduced-fat dairy intake on measures of adiposity and biomarkers of cardiometabolic risk in healthy 4- to 6-y-old children. Methods: The Milky Way Study enrolled 49 children (mean ± SD age: 5.2 ± 0.9 y; 47% girls) who were habitual consumers of whole-fat dairy, then randomly assigned them in a double-blind fashion to remain on whole-fat dairy or switch their dairy consumption to reduced-fat products for 3 mo. Primary endpoints included measures of adiposity, body composition, blood pressure, fasting serum lipids, blood glucose, glycated hemoglobin (HbA1c), and C-reactive protein (CRP) and were assessed at baseline and study end. Pre- and postintervention results were compared using linear mixed models, adjusted for growth, age, and sex. Results: Dairy fat intake was reduced by an adjusted (mean ± SEM) 12.9 ± 4.1 g/d in the reduced-fat compared with the whole-fat dairy group (95% CI: –21.2, –4.6 g/d; P = 0.003), whereas dietary energy intakes remained similar ( P = 0.936). We found no significant differential changes between dairy groups in any measure of adiposity, body composition, blood pressure, or fasting serum lipids, glucose, HbA1c, and CRP. Conclusions: Our results suggest that although changing from whole-fat to reduced-fat dairy products does reduce dairy fat intake, it does not result in changes to markers of adiposity or cardiometabolic disease risk in healthy children. This trial was registered at www.anzctr.org.au as ACTRN12616001642471.